Layu Sebelum Berkembang: Sejarah dan Penyebab Gagalnya Bank Sampah di Desa Bambangin Kabupaten Barito Kuala - Aziziah, Nor; Zulaikha, Siti (Huma: Jurnal Sosiologi, 2025)
Waste management in Bambangin Village, located along the riverbank, has become a major issue. To address this, a Waste Bank program was initiated as a community-based solution. This study aims to analyze the formation and sustainability of the program through the lens of community empowerment. A qualitative, descriptive approach was used, with data analyzed using an interactive model that includes data collection, reduction, presentation, and conclusion. The Waste Bank was launched by the village head in response to the village’s growing waste problem. It functioned effectively in 2023, but ceased operation in 2024 due to several challenges. The program’s collapse followed the death of the village head, the inability of the management team to continue, a lack of funding, minimal external support, and weak community commitment. The failure was also linked to poor community engagement and the absence of enabling conditions for sustainable participation. The community was not adequately equipped with the skills and knowledge necessary for independent waste management. Without practical experience in Waste Bank operations, empowerment efforts fell short. Consequently, improper waste disposal resumed, leading to environmental pollution. This research highlights key challenges and reasons behind the program’s failure, offering valuable lessons for similar initiatives in the future. Further studies should focus on developing sustainable strategies involving stakeholders, exploring funding models, and implementing effective education to boost community participation and ensure the long-term success of Waste Bank programs.